2019
DOI: 10.1111/vcp.12733
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of automated erythrocyte methodology in new world camelids using the ADVIA 2120 hematology analyzer

Abstract: Background: Accurate erythrocyte measurements with ADVIA hematology analyzers require isovolumetric cell sphering in one reaction and hemolysis in another.However, camelid erythrocytes are resistant to sphering and osmotic lysis, and no published evaluation of ADVIA methods for camelids exists. Objectives:The objectives were to demonstrate whether camelid erythrocytes sphere in the ADVIA red blood cell/platelet (RBC/PLT) reagent and lyse in the ADVIA cyanide HGB reagent, and to determine optimal ADVIA settings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Additionally, before the initial drug administration (day 1), on the day of the last dose (day 5), and 5 days after the last dose (day 10), whole blood was collected into a tube containing ethylenediaminetetraacetic acid (EDTA) anticoagulant for complete blood count (CBC) and a tube containing heparin anticoagulant for plasma chemistry testing. These samples were submitted to the University of Tennessee Veterinary Medical Center (UTCVM) clinical pathology laboratory, with testing performed according to the laboratory standard operating procedure using an ADVIA 2,120 hematology analyzer (Siemens, Munich, Germany) and a Cobas C501 chemistry analyzer (Roche Diagnostics, Basel, Switzerland) (20).…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, before the initial drug administration (day 1), on the day of the last dose (day 5), and 5 days after the last dose (day 10), whole blood was collected into a tube containing ethylenediaminetetraacetic acid (EDTA) anticoagulant for complete blood count (CBC) and a tube containing heparin anticoagulant for plasma chemistry testing. These samples were submitted to the University of Tennessee Veterinary Medical Center (UTCVM) clinical pathology laboratory, with testing performed according to the laboratory standard operating procedure using an ADVIA 2,120 hematology analyzer (Siemens, Munich, Germany) and a Cobas C501 chemistry analyzer (Roche Diagnostics, Basel, Switzerland) (20).…”
Section: Methodsmentioning
confidence: 99%
“…Underfilled, clotted, or lipemic samples were excluded. A CBC was performed on each sample using the ADVIA120 hematology instrument (Siemens Healthcare Diagnostics, Tarrytown, NY), and samples were excluded if the PCV, HGB, or RBC were below the UTVMC reference intervals for camelids.…”
Section: Methodsmentioning
confidence: 99%
“…Viesselmann et al ( 2019a ) studied RBC parameters in 25 SACs in an analyser (ADVIA 2120), they observed significant deviations in MCV and MCHC from the reference method in two animals with fatal anaemia (PCV: 0.07 l/l and 0.08 l/l). Vap and Bohn ( 2015 ) also report falsely elevated MCHC in the automated measurement of blood samples from SACs and attribute this to the fact that in some cases too few erythrocytes have been collected.…”
Section: Problems With Automated Measurement Of Anaemic Blood Samplesmentioning
confidence: 99%